Radiation Therapy Resources and Guideline‐Concordant Radiotherapy for Early‐Stage Breast Cancer Patients in an Underserved Region. (28th February 2013) - Yao, Nengliang; Matthews, Stephen A.; Hillemeier, Marianne M.; Anderson, Roger T.
Abstract : Objective: To examine the relationship between radiation therapy resources and guideline‐concordant radiotherapy after breast‐conserving surgery (BCS) in Kentucky. Data Sources: The SEER registry and Area Resource File provided county‐level data describing cancer care resources and socioeconomic conditions of Kentucky residents. Study Design: The outcome variable was rate of BCS without radiotherapy in each county for 2000–2007. Eight‐year weighted average rates of radiation therapy providers and hospitals per 100, 000 residents were explanatory variables of interest. Exploratory spatial data analyses and spatial econometric models were estimated. Principal Findings: Appalachian counties in Kentucky had significantly fewer radiation oncologists, hospitals with radiation therapy facilities, and surgeons per 100, 000 residents than non‐Appalachian counties. The likelihood of BCS without radiation was significantly higher among Appalachian compared to non‐Appalachian women (42.5 percent vs. 29.0 percent, p  < .001). Higher proportions of women not receiving recommended radiotherapy after BCS were clustered in Eastern Kentucky around Lexington. This geographic disparity was partially explained by significantly fewer radiation therapy facilities in Appalachian Kentucky in adjusted analyses. Conclusions: Scarce radiation therapy resources in Appalachian Kentucky are associated with disparities in receipt of guideline‐concordant radiotherapy, suggesting that policy action is needed to improve the cancer treatment infrastructure in disadvantaged mountainous areas.